Global or local - glocalization as a challenge for the modern supply chains management - Dymyt Małgorzata; Wincewicz-Bosy Marta; Skubisz Oskar (2024)
This article focuses on issues of designing, supply chains in the context of the spatial scope of operation, and dilemmas related to the choice between global and local activities. The research niche of this article is the phenomenon of glocalization. The review focuses on two aspects - the essence and dimensions of supply chain configuration (global and local) and how a glocalization approach that takes into account the combination of these dimensions can support the adaptability and resilience of supply chains. The considerations are set in the pharmaceutical industry. The purpose of this paper is twofold. Firstly, identifying the challenges and directions of development of supply chain management and presenting the essence and role of glocalization, and secondly, defining the key factors for configuring supply chains in the pharmaceutical industry, especially in the context of glocalization. A qualitative research approach was used to solve the research problem, referring to the relevant literature in the field of supply chain management and the functioning of the pharmaceutical industry in Poland. The main conclusion concerns the statement that the design and management of modern, resilient and adaptive supply chains requires combining a global approach, integrated at the international or global level, with an approach focused on the needs of local markets. The pharmaceutical industry faces the challenge of harmoniously combining global ambitions with local realities. Glocalization in the pharmaceutical industry emphasizes that success on the global market requires the ability to flexibly and effectively respond to diverse and changing local contexts.